12 Reflections on palliative care health care professionals' needs during the first wave of the Covid-19 pandemic 'thematic analysis of a postgraduate cohort of students' discussion board. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Rawlinson, Fiona; Smith, Ross; Dinnen, Toby; Hayes, Ed; Harper, Karianne; Duffy, Tony; Jones, Tamarha; Thomas, Lucy; Clarke, Jo; Joad, Anjum; Iyer, Rajam; Marcheant, Rachael; et al.
Abstract : background/Introduction: The Covid-19 pandemic created immense unexpected pressure on postgraduate health care professional students undertaking academic study. The role of a community of practice within an international cohort of postgraduate students became apparent as the pandemic progressed. Needing a supported space away from social media in which to discuss developing issues, and a forum in which useful resources could be shared swiftly became apparent. A closed 'Discussion board' facility was used within the virtual learning platform in which themes and collections of support, ideas and materials were developed. Methods: Qualitative thematic analysis of anonymised contributions to the Discussion board 25th March 2020 - 31st July 2020. Permission was sought retrospectively from all participants on the Discussion Board; any information from those not willing for their content to be included was deleted from the transcripts before review. The transcripts were reviewed by 2 independent researchers for content and context. Results: 13 themes developed. Sharing resources (March); ethical issues, communication skills (including virtual communication), symptom control, team support and leadership, the challenge of covid 19 in remote communities, the collateral damage of the pandemic for children, involving the family remotely and maintaining one's own wellbeing in a pandemic ( April); Developing services, moving forward and quality improvement ( May); moral courage and managing the symptom of breathlessness (June). Conclusions: The generation of themes reflected the unprecedented challenges of the phase of the pandemic being experienced. Symptom control, communication skills and ethics leading to their application in different settings and the need after the first few weeks for team support, mental resilience and leadership. Valuable reflections and resources have been developed to help support future surges.